The control of identity for the location of persons with order capture in the Judicial District of Huánuco. 2016 - Huaman-Santamaria, Luis E. (2019)
The present investigation was as objective to determine the influence on the actions of police personnel in the execution of the operations of identity control with the inclusion of the purpose" location of persons with arrest warrant "of article 205 of the Code of Criminal Procedure. Of applied type, descriptive-correlational level, non-experimental descriptive, transverse, correlational design. The population was made up of 110 police personnel and the sample conformed by the same population. As a result, the actions of police personnel have a positive influence on the execution of identity control operations with the inclusion of the purpose "location of persons with arrest warrants" in article 205 of the Code of Criminal Procedure, since 87% of The police officers believe that the actions are efficient, 11% believe that they are regularly efficient and 2% believe that they are deficient. This influence is based on the hypothesis test where in the resulting model is: Vd = 0.412Vi - 0.596; It is observed that there is a positive influence between the actions of police personnel and the inclusion of the purpose "location of persons with arrest warrants". Just as the ratio has a value of 0.844 and the coefficient of determination (R squared) is 0.713 (71.3%) indicates that the resulting model determines a high adjustment of police personnel and the inclusion of the purpose of "location of persons with capture order ", where the influence is 71.3%.